Announcement—guidance document for acquiring reliable data in ecological restoration projects. Issue 5 (16th May 2016) - Stapanian, Martin A.; Rodriguez, Karen; Lewis, Timothy E.; Blume, Louis; Palmer, Craig J.; Walters, Lynn; Schofield, Judith; Amos, Molly M.; Bucher, Adam
Abstract : The Laurentian Great Lakes are undergoing intensive ecological restoration in Canada and the United States. In the United States, an interagency committee was formed to facilitate implementation of quality practices for federally funded restoration projects in the Great Lakes basin. The Committee's responsibilities include developing a guidance document that will provide a common approach to the application of quality assurance and quality control (QA/QC) practices for restoration projects. The document will serve as a "how‐to" guide for ensuring data quality during each aspect of ecological restoration projects. In addition, the document will provide suggestions on linking QA/QC data with the routine project data and hints on creating detailed supporting documentation. Finally, the document will advocate integrating all components of the project, including QA/QC applications, into an overarching decision‐support framework. The guidance document is expected to be released by the U.S. EPA Great Lakes National Program Office in 2017.